2018
DOI: 10.2147/cmar.s175780
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma fibrinogen in hepatocellular carcinoma: a meta-analysis

Abstract: BackgroundElevated plasma fibrinogen levels have been associated with tumor progression in several malignancies. Our study aims to characterize the clinical significance of elevated plasma fibrinogen levels in patients with hepatocellular carcinoma (HCC).Materials and methodsRelevant published articles were systematically searched in electronic databases including PubMed, Embase, and Web of Science. The pooled differences in plasma fibrinogen levels among HCC, cirrhotic, and control groups were expressed as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…18 As a hemostatic factor, fibrinogen is the critical and decisive factor of tumor cell's metastasis potency, for it can combine with other proteins and deposit on the extracellular matrix, and then functioning as a scaffold, which can combine with the growth factors, as a result, promotes cell proliferation, adhesion and tumor metastasis. 19 Studies have shown that elevated serum fibrinogen levels are associated with poor prognosis in patients with liver cancer, [20][21][22] esophageal cancer, 23 ovarian cancer. 24 The involvement of lymphocytes in the immune function plays an extremely important role in many aspects, such as tumor immunization assessment 25 and immunological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…18 As a hemostatic factor, fibrinogen is the critical and decisive factor of tumor cell's metastasis potency, for it can combine with other proteins and deposit on the extracellular matrix, and then functioning as a scaffold, which can combine with the growth factors, as a result, promotes cell proliferation, adhesion and tumor metastasis. 19 Studies have shown that elevated serum fibrinogen levels are associated with poor prognosis in patients with liver cancer, [20][21][22] esophageal cancer, 23 ovarian cancer. 24 The involvement of lymphocytes in the immune function plays an extremely important role in many aspects, such as tumor immunization assessment 25 and immunological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Over the last few years, numerous scholars have devoted themselves to studying some markers that are associated with the early recurrence of patients with HCC after TACE or curative ablation therapy, including tumor number, fibrinogen (Fib), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and so on. 10,11 Nevertheless, relevant studies on combined therapies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have discovered that the coagulation system is overly activated in many cancers, such as lung cancer [8,9], hepatocellular carcinoma [10,11], pancreatic cancer [12], and oesophageal cancer [13,14] and so on, but data about cancers of the urinary system, especially renal cell carcinoma, are still lacking. Jun Du [15] enrolled 286 patients receiving radical nephrectomy and retrospectively evaluated the association of preoperative plasma fibrinogen level with the clinicopathological parameters and survival.…”
Section: Discussionmentioning
confidence: 99%